Real-world Outcomes With Rituximab-based Therapy for Posttransplant Lymphoproliferative Disease Arising After Solid Organ Transplant. Issue 12 (December 2020) - Burns, David M.; Clesham, Katherine; Hodgson, Yan A.; Fredrick, Lynsey; Haughton, Joanna; Lannon, Michelle; Hussein, Hayder; Shin, Jin-Sup; Hollows, Robert J.; Robinson, Lisa; Byrne, Catherine; McNamara, Christopher; et al.
Abstract : Background: Optimal upfront therapy for posttransplant lymphoproliferative disease (PTLD) arising after solid organ transplant remains contentious. Rituximab monotherapy (R-Mono) in unselected patients has shown a lack of durable remissions. Cyclophosphamide, doxorubicin, vincristine, and prednisolone (CHOP)-based chemotherapy confers improved response rates, although concerns exist about toxicity. Methods: This multicenter retrospective study reports outcomes for adults with biopsy-proven B-cell PTLD treated initially with R-Mono or Rituximab plus CHOP (R-CHOP). Selection of therapy was made according to physician preference. Results: Among 101 patients, 41 received R-Mono and 60 had R-CHOP. Most (93%) had undergone renal or liver transplantation. R-CHOP showed a trend toward improved complete (53% versus 71%; P  = 0.066) and overall (75% versus 90%; P  = 0.054) response rates. In the R-Mono group, 13 of 41 (32%) subsequently received chemotherapy, while 25 of 41 (61%) remained progression-free without further therapy. With median follow-up of 47 months, overall survival (OS) was similar for R-Mono and R-CHOP, with 3-year OS of 71% and 63%, respectively ( P  = 0.722). Non-PTLD mortality was 3 of 41 (7%) and 4 of 60 (7%) within 12 months of R-Mono or R-CHOP, respectively. The International Prognostic Index was statistically significant, with low- (0–2 points) and high-risk (≥3 points) groups exhibiting 3-year OS of 78% and 54%, respectively ( P  = 0.0003). In low-risk PTLD, outcomes were similar between therapies. However, in high-risk disease R-Mono conferred an inferior complete response rate (21% versus 68%; P  = 0.006), albeit with no impact on survival. Conclusions: Our data support R-Mono as initial therapy for PTLD arising after renal or liver transplantation. However, upfront R-CHOP may benefit selected high-risk cases in whom rapid attainment of response is desirable. Abstract : Supplemental Digital Content is available in the text.